As desigualdades sociais na educação e seus impactos sobre o processo de evasão e retenção dos alunos do ensino médio integrado em um Instituto Federal no período de pandemia - Farias, Érica Oliveira de Castro (2023)
The present study “Social inequalities at education and their impacts on the process of dropout and retention of high school students integrated into a Federal Institute during the pandemic period”. Its general objective is to understand how social inequalities are linked to the increase in dropout and retention of integrated high school students amid the new coronavirus pandemic scenario. The specific objectives are: a) Identify how the social context in which the student lives (situations of hunger, violence, unemployment) affect their academic life; b) Map out the main reasons that lead integrated high school students to drop out or get stuck; c)Evaluate whether the Student Assistance Policy contributed to preventing and/or alleviating dropout and retention situations during the pandemic period; d)Develop an educational product that provides preventive work to reduce dropout and retention levels in integrated secondary education during the pandemic period. As a research sample, we will have four (04) (former) students and two (02) students retained in the series of Secondary Level Technical Courses in Integrated Forms, in addition to two (02) pedagogues and two (02) social workers who do the pedagogical and social monitoring at IFAM/Campus Manaus-Centro, totaling 10 (ten) subjects. The research has a qualitative approach, structured in a case study, and is applied in nature. Field diaries based on observations, questionnaires and interviews will be used as data collection instruments. The collected data will be analyzed using Discursive Textual Analysis (ATD) according to Moraes and Galiazzi (2011), following the three (03) steps that make up the analysis cycle: 1) disassembling the texts, also called unitarization; 2) establishing relationships, called categorization and 3) capturing the emerging new that materializes in metatexts. The results obtained from the research indicate that social inequalities have a direct impact on school dropout and retention on the Manaus-Center campus and that it adds to other factors that concern the Institution itself in its way of organizing itself and dealing with demands. from the students. Given this result, an Educational Product entitled AJURI was developed: practical guide for reducing dropout and school retention at IFAM Campus Manaus - Center to be used by the academic community, especially teachers, on how social inequalities manifest themselves in the school environment, leading to evasion and retention in times of pandemic.